Relationship of anti-tuberculosis drug-induced liver injury and genetic polymorphisms in CYP2E1 and GST - Eliana Abreu Santos; José Carlos Saraiva Gonçalves; Marcos K. Fleury; Afrânio L. Kritski; Martha M. Oliveira; Luciane S. Velasque; José Roberto Lapa e Silva; Rita de Cássia E. Estrela (Brazilian Journal of Infectious Diseases, 2019)
Setting: Treatment of tuberculosis (TB) can result in Drug-Induced Liver Injury (DILI) since hepatotoxic metabolites are formed during the biotransformation of isoniazid (INH).DILI can be related to the genetic profile of the patient. Single nucleotide polymorphisms in the CYP2E1 gene and GSTM1 and GSTT1 deletion polymorphisms have been associated with adverse events caused by INH. Objective: To characterize the genetic polymorphisms of CYP2E1, GSTT1 and GSTM1 in TB carriers. Design: This is an observational prospective cohort study of 45 patients undergoing treatment of TB. PCR-RFLP and multiplex-PCR were used. Results: The distribution of genotypic frequency in the promoter region (CYP2E1 gene) was: 98% wild genotype and 2% heterozygous. Intronic region: 78% wild genotype; 20% heterozygous and 2% homozygous variant. GST enzyme genes: 24% Null GSTM1 and 22% Null GSTT1. Patients with any variant allele of the CYP2E1 gene were grouped in the statistical analyses. Conclusion: Patients with the CYP2E1 variant genotype or Null GSTT1 showed higher risk of presenting DILI (p = 0.09; OR: 4.57; 95% CI: 0.75–27.6). Individuals with both genotypes had no increased risk compared to individuals with one genotype. Keywords: Adverse event, Polymorphisms of CYP2E1 and GST, Induced liver injury from treatment of tuberculosis, Hepatotoxicity, Pulmonary tuberculosis